Contextualising the Muizenberg Civic Centre: an investigation into urban and environmental integration - Schofield, Amy (School of Architecture, Planning and Geomatics, 2023)
The Muizenberg Civic Centre currently expels an attitude of inhospitality and abandonment which has resulted in its utter lack of interaction with, and use by, the community. Hence, it acts as both a physical and visual blockade between the bustling Surfer's Corner and the forsaken open air amusement park. This paper aims to utilise the sustainable practice of adaptive reuse to articulate a design that allows the Muizenberg Civic Centre to seamlessly integrate into both its surrounding urban and natural context. This is achieved by first understanding its physical, social and architectural context before analysing the opportunities and challenges that the site and surrounding urban fabric presents. It extracts lessons from Muizenberg Civic Centre replicas, Fish Hoek Beach and the Sea Point Promenade to inform both the urban and site design proposals that are innately driven by the desire for integration and accessibility, whilst taking full advantage of its prime beachfront location.